The acquisition value of oil and gas firms: The role of historical costs, reserve recognition accounting, and analysts' appraisals* - GHICAS, DIMITRIOS; PASTENA, VICTOR (Contemporary Accounting Research, 1989)
Abstract. Our research confirms that book values possess significant ability to explain the acquisition values of oil and gas firms. It also indicates that RRA information provides incremental information over book values in determining acquisition values. However, when analyst information is more current than competing information, analysts' appraisals provide a significant incremental contribution beyond the explanatory ability of book values and reserve recognition data. Current analysts' information provides a stronger basis for predicting acquisition values than any model supplementing analysts' appraisals with additional information. This implies that current analysts' information captures all information sources and is consistent with the findings of “analysts superiority” in the extensive literature on earnings forecasts. Résumé. Les travaux des auteurs confirment que les valeurs comptables peuvent assez bien expliquer les valeurs d'acquisition des entreprises pétrolierès et gazières. Ils révèlent également que les renseignements livrés par la méthode de la capitalisation des gisements fournissent de l'information marginale par rapport aux valeurs comptables dans la détermination des valeurs d'acquisition. Toutefois, lorsque l'information des analystes financiers est plus récente que l'information concurrente, les évaluations des analystes apportent une contribution marginale importante au‐delà de la capacité explicative des valeurs comptables et de données relatives à la capitalisation des gisements. L'information récente des analystes offre une base plus solide pour la prévision des valeurs d'acquisition que tout modèle qui sert de complément aux évaluations des analystes. Cela suppose que l'information récente des analystes recouvre toutes les sources d'information et vient confirmer la conclusion reconnaissant la «supériorité des analystes » à laquelle se range une abondante documentation sur les prévisions de résultats.